Water mass transformation in the Iceland Sea: contrasting two winters separated by four decades - Våge, Kjetil; Semper, Stefanie; Valdimarsson, Héðinn; Jónsson, Steingrímur; Pickart, Robert S.; Moore, G. W. K. (Deep Sea Research Part I: Oceanographic Research Papers, 2022)
© The Author(s), 2022. This article is distributed under the terms of the Creative Commons Attribution License. The definitive version was published in Våge, K., Semper, S., Valdimarsson, H., Jónsson, S., Pickart, R., & Moore, G. Water mass transformation in the Iceland Sea: contrasting two winters separated by four decades. Deep Sea Research Part I: Oceanographic Research Papers, 186, (2022): 103824, https://doi.org/10.1016/j.dsr.2022.103824. Dense water masses formed in the Nordic Seas flow across the Greenland–Scotland Ridge and contribute substantially to the lower limb of the Atlantic Meridional Overturning Circulation. Originally considered an important source of dense water, the Iceland Sea gained renewed interest when the North Icelandic Jet — a current transporting dense water from the Iceland Sea into Denmark Strait — was discovered in the early 2000s. Here we use recent hydrographic data to quantify water mass transformation in the Iceland Sea and contrast the present conditions with measurements from hydrographic surveys conducted four decades earlier. We demonstrate that the large-scale hydrographic structure of the central Iceland Sea has changed significantly over this period and that the locally transformed water has become less dense, in concert with a retreating sea-ice edge and diminished ocean-to-atmosphere heat fluxes. This has reduced the available supply of dense water to the North Icelandic Jet, but also permitted densification of the East Greenland Current during its transit through the presently ice-free western Iceland Sea in winter. Together, these changes have significantly altered the contribution from the Iceland Sea to the overturning in the Nordic Seas over the four decade period. Support for this work was provided by the Trond Mohn Foundation, Norway under grant BFS2016REK01 (K.V. and S.S.), the European Union’s Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement no. 101022251 (S.S.), the US National Science Foundation under ...